SETS Learning Efficacy to Improve Students Science Literacy Skills - Ristina, Hayu; Linuwih, Suharto; Nuswowati, Murbangun (Journal of Innovative Science Education, 2019)
Science learning aims to help students to be able to master the knowledge of scientific order. Science learning will be more meaningful for students, if students have good literacy skills. Someone has scientific literacy skills that can both understand and communicate science, and applying science knowledge in solving problems, and can make decisions based on scientific considerations. The results of international research show that the literacy rate of Indonesian students is in the low category. This study aims to determine the effectiveness of SETS learning to improve students' scientific literacy skills. The design of this study used quasi experimental with non-equivalent control group design. In general, the results of the study show that the effectiveness of SETS learning can be seen based on student learning outcomes in the experimental class showing better than control class students and increasing scientific literacy skills in each of the relatively high categories. Science literacy skills in the interaction of science, technology, and society experienced the highest increase in ability compared to other scientific literacy categories.